A Critical Analysis of Effectiveness of Anti-Corruption Laws in Pakistan: Policy Recommendations - Akram, Rehan (Journal of Public Policy Practitioners, 2023)
This policy paper attempts to gauge the effectiveness of anti-corruption laws in Pakistan designed to address the menace of corruption. For this purpose, the challan and conviction data of NAB, FIA, and ACE (Punjab) over the past few years has been analyzed. It has been observed that the change in NAB law in 2021 and 2022 had a significantly negative impact on both the number of challans / references filed by NAB and conviction ratios. The analysis of the amended NAB law shows its inherent deficiencies in addressing the offenses related to assets beyond means and misuse of authority. Furthermore, the predominant law of both FIA and ACE – Prevention of Corruption Act, 1947 – is unable to deal with the complexities of the 21st century, thus significantly impacting the conviction ratios of these agencies. It is also discussed that the countries with very low CPI, such as Singapore, have a broad perspective regarding the definition of corruption which is lacking in our national anti-corruption legal framework. The policy paper also discusses the preventive approach of Hong Kong to combat corruption, both, at legislative and strategic levels. Based on analysis and discussion, this research recommends necessary rectifications in the anti-corruption legal framework of the country to make it effective in curbing the prevalence of corruption in Pakistan.